CORPUS ANALYSIS OF SPEECH UNITS IN SOCIAL NETWORKS («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article describes the use of an electronic database to study and verify the analysis of speech units in social media with the help of a corpus, the identification of marked speech changes, their specific characteristics and the reasons for their changes.
Keywords: NLP, API, Twitter, Reddit, Facebook, LinkedIn.